The Implementation of selective method of Mutholaah lesson at Darussalam Gontor - Mandrasi Amira saidah; Heru Saiful Anwar; Fairuz Subakir (At-Ta'dib, 2020)
Arabic is the language that must be owned and acquired by all Muslims, and its advantage has made Arabic better and better than other languages, and it differs in another language. Because it pushed the laws of the symbol specific in the pronunciation of its people and non-native speakers or made it a machine for communication between them because it is a language that was lowered in the language of the Holy Quran.Especially in the Arabic reading lesson, because it has an important role in promoting Arabic at this institute. The researcher presented the goal of the research, which is to reveal the implementation of the methods, methods and entrances used in reading education for class four of Islamic teachers at the Darusalam Gontor for Girls First campus.This research was a field research by a descriptive qualitative study. The researcher collected the preliminary data consisting of written documents and so on as it is relevant, in the collection of data, the researcher used the method of written documents and the method of interviewing and observation, and in her analysis of the research the researcher took the method of Miles & huberman, and this was The analysis consists of three plans: data reduction, data presentation and analysis, and inference. Keywords : Implementation,  selective method, Mutholaah lesson